Računalniško vodeno predoperativno načrtovanje in vsaditev zobnih implantatov - Grošelj, Dušan (Zdravniški vestnik, 2007)
Background Implants in dentistry are, besides fixed, removable and maxillofacial prosthodontics, one of the reliable possibility to make functional and aesthetic rehabilitation of the edentulism. Surgical and prosthodontic implant complications are often an inattentive consequence of wrong diagnosis, planning, and placement. In this article we present a technique using a highly advanced software program along with a rapid prototyping technology named stereolithography. A planning software for implant placement needs basically the high quality computed tomographic scan of one or both jaws for making accurate preoperative diagnostics and 3D preoperative plan. Later individual drill guide is designed and generated based on both the CT images and the preoperative planning. The patient specific drill guide transfers the virtual planning to the patient's mouth at time of surgery. Conclusions The advantages of computer guided implantology are the better prepared surgery with visualisation of critical anatomic structures, assessment of available bone and data about bone quality, increased confidence for the surgeon, deceased operative time, less frequent use of bone grafts, higher quality of collaboration between specialists and prosthetic lab and better communication with patients. Radiographic examination of the operation field for computer guided planning for implant placement is due to high costs justified as the most important information source on the areas to be implanted.
Keywords: Čeljust; Dental Implantation; Dental Implants; implantati; Jaw; kirurško zdravljenje; Methods; načrtovanje; računalniško načrtovanje; Radiography; stomatologija; Therapy, Computer-Assisted; Tomografija radiografska, računalniška; Tomography, X-Ray Computed; Zdravljenje z računalnikom; Zob, vsaditev; zobje; Zobni vsadki